SISTEM PEWARISAN DALAM PERKAWINAN ANTARA SUKU BATAK DAN SUKU MINANGKABAU (STUDI DI KOTA MEDAN) - ULFA SUNDARI (PREMISE LAW JURNAL, 2018)
The problems of allocation of an inheritance will never cease when they are analyzed based on the system of kinship which is practiced either by a certain traditional community or by the community that follows the bonds of matrimony with different kinship such as in interracial marriage. The research used descriptive analytic method which described, explained, and analyzed inheritance system in the intermarriage between a Bataknese and a Minangkabaunese.The result of the research showed that the existence of various kinds of ethnic groups in Indonesia had caused intermarriages with different kinship so that the allocation of inheritance from parents to their children would change. The allocation of inheritance in the community that practices patrilineal system has changed in which the allocation of inheritance in the intermarriage of the patrilineal community usually uses individual inheritance system of the Adat Law although some of them use inheritance system based on the Islamic Law. The allocation of inheritance in the community that practices matrilineal system, although the parties concerned come from matrilineal kinship system, when there is intermarriage, the kinship system is not used. The allocation of inheritance is done according to the agreement of the heirs as what is practiced in the patrilineal system. This system has also been changed in the inheritance allocation system which is done either according to the mutual agreement or to the Islamic Law.Keywords: Inheritance System in Bataknese and Minangkabaunese